Peran Bahan Ajar Multikeaksaraan Berbasis Potensi Lokal dalam Meningkatkan Profesi Warga Belajar di Masyarakat - Sabighoot, Yus Alvar; Suminar, Uum; Hisyam, Mohamad (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2023)
Multiliteracy education is an educational service that organizes learning for students who have completed basic literacy education. Multiliteracy education known as post literacy can be seen as a concept, process and program. In practice, teaching materials play a very important role in achieving educational attainment. This study uses a qualitative approach and descriptive method. Data collection techniques used are through interviews, observation, and documentation. The research locations are in 4 PKBMs in the districts/cities of Banten Province which are areas for PBL development in multiliteracy education in the PNF unit. It was concluded that the role of teaching materials based on local potential plays an important role in the professional development of students in the community. There are 3 main components to be assessed, namely the ability to read, count, write, and have local potential livelihoods/professions. Where it was produced that the usefulness of this teaching material was very good starting from the attractiveness and ease of the guide each getting a percentage of 63.3% and 51.7%. So that it can be said that multiliteracy teaching materials based on local potential can indeed improve the ability to maintain advanced literacy and the profession of students according to their local potential in society.